Zip‐related genital injury. (13th March 2013) - Bagga, Herman S.; Tasian, Gregory E.; McGeady, James; Blaschko, Sarah D.; McCulloch, Charles E.; McAninch, Jack W.; Breyer, Benjamin N.
<x xml:space="preserve">Abstract</x> Objective To describe the epidemiology of genital injuries caused by trouser zips and to educate both consumers and the caregivers of patients who sustain such injuries. Patients and Methods The National Electronic Injury Surveillance System, a dataset validated to provide a probability sample of patients who present to emergency departments (EDs) in the USA with injuries, was analysed to characterize zip‐related genital injuries occurring between 2002 and 2010. A total of 523 cases were analysed to obtain national estimates. Results Between 2002 and 2010, an estimated 17 616 patients presented to US EDs with trouser zip injuries to the genitals. The penis was almost always the only genital organ involved. Zip injuries represented nearly one‐fifth of all penile injuries. Amongst adults, zips were the most frequent cause of penile injuries. Annual zip‐related genital injury incidence remained stable over the study period. Conclusions Zip‐related genital injuries affect both paediatric and adult cohorts. Practitioners should be familiar with various zip‐detachment strategies for these populations.